2021
DOI: 10.1186/s13018-021-02513-3
|View full text |Cite
|
Sign up to set email alerts
|

Conservative versus tailored surgical treatment in patients with first time lateral patella dislocation: a randomized-controlled trial

Abstract: Background Patellar instability has a high incidence and occurs particularly in young and female patients. If the patella dislocates for the first time, treatment is usually conservative. However, this cautious approach carries the risk of recurrence and of secondary pathologies such as osteochondral fractures. Moreover, there is also risk of continuous symptoms apparent, as recurrent patella dislocation is related to patellofemoral osteoarthritis as well. An initial surgical treatment could po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
0
16
0
1
Order By: Relevance
“…Nevertheless, more than two-thirds of the patients presenting recurrent patellar dislocations demonstrate two or more pathoanatomical predisposing factors, which may synergistically predispose them to joint instability [64][65][66]. The association of additional procedures is still debated and should be evaluated at an individual level [1,67]. Six of eight studies were case…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, more than two-thirds of the patients presenting recurrent patellar dislocations demonstrate two or more pathoanatomical predisposing factors, which may synergistically predispose them to joint instability [64][65][66]. The association of additional procedures is still debated and should be evaluated at an individual level [1,67]. Six of eight studies were case…”
Section: Discussionmentioning
confidence: 99%
“…With the development of algorithmic classification systems and a better understanding of the individual pathogeneses, surgical treatment of patellofemoral instabilities has become more precise [ 11 , 12 ]. Several clinical studies have outlined the effectiveness of procedures, such as trochleoplasty [ 42 , 43 ], torsional DFO [ 16 , 44 ], varizating DFO [ 26 , 45 ], or tibial tubercle transfer [ 14 , 46 , 47 ], in terms of redislocation rates, improvement of clinical scores, or return to activity.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was confirmed by multiple biomechanical investigations that demonstrated direct alterations of patellar tracking when certain risk factors were present [ 6 , 7 , 8 , 9 , 10 ]. On the basis of these findings, modern surgical approaches are aimed at identifying and addressing all relevant pathologies in the affected knee [ 11 , 12 , 13 ]. In the recent literature, several clinical studies have examined the postoperative success of individualized patellofemoral surgery, and most of these studies reported improved patient-reported outcome measures (PROMs) and low redislocation rates [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is disagreement about what procedure is indicated after the index injury. 23 , 24 Surgery needs to be considered individually for every patient. However, given that 50% to 70% of the children with first acute patellar dislocation will resolve without a second dislocation, routine corrective operation will not be justified for all patients.…”
Section: Assessment and Investigationmentioning
confidence: 99%